Evaluasi Pemupukan Urea Lahan Sawah Tadah Hujan Untuk Tanaman Padi - Kasno, Antonius; Rostaman, Tia (Jurnal Penelitian Pertanian Tanaman Pangan, 2017)
Nitrogen is the main macro nutrients that are needed rice crops, without it the yield of rice equal with rice without fertilizers. Fertilization without taking into consideration characteristics of the soil  caused changes in soil nutrient imbalances. Response of plant to nitrogen fertilization changed the imbalance  nutrient in the soil, so the evaluation of urea fertilization need to be done. The aim of this paper is to evaluate the urea fertilization for rice in rainfed areas. The study was conducted in six locations  Andong, Jakenan, Cibeber, Gabus, Panimbang and Sukadana during the dry season in 2015 and 2016. Urea fertilization is part of the N, P, K fertilizer experiment which carried out with a  randomized complete block design with four levels of N fertilizer dose. The dose level of N fertilizer were 0, 200, 300, and 400 kg urea/ha, which is repeated three times. In addition to urea as treatment, each plot of treatment added 125 kg SP-36 and 100 kg KCl per ha. The results showed that the majority of the rainfed areas containing N low. N fertilizer significant increased of plant height between 12.9 – 32.4 cm, number of tillers from 3.3 to 8.6 stems, weight of dried grain harvest from 1.93 – 5.00 t/ha, weight of grain dry milled 1.52-2.59 t/ha, and dry straw weight increase between 2.29 to 3.17 t/ha. The optimum dose of urea fertilizer for rice rainfed areas ranged between 200-300 kg urea/ha. Dose of fertilizer based on productivity of the rice is still relevant is used as a basis for the create of urea fertilizer recommendation.